Post-deposition annealing effect on the structural and electrical properties of Ytterbium oxide as an alternative gate dielectric - Morkoc, Berk; Kahraman, Aysegul; Yilmaz, Ercan (Elsevier Science Sa, 2022)
The possibility of ytterbium(III) oxide, one of the rare earth oxides, to replace silicon dioxide used as the gate dielectric is discussed in this article. For such a replacement, it is primarily necessary to understand the physical and chemical characteristics of ytterbium(II) oxide as a candidate, such as bond structure, electronic structure, band offsets with Si, dielectric constant, interfacial states and defect behavior. The effects of structural and electrical features of ytterbium(III) oxide-based MOS capacitors on device performance are investigated. The electron beam physical vapor deposition (EBPVD) technique was used for the deposition of ytterbium(III) oxide thin films. The 122 nm thick Yb2O3 thin film was annealed at four different temperatures (200 degrees C, 400 degrees C, 600 degrees C, and 800 degrees C) in nitrogen environment. The crystallite size determined from the as-deposited sample as 15 nm is the lowest. As expected, crystallite sizes increased as a result of increasing annealing temperature. The presence of Yb2+ oxidation states increased in the region close to the interface or at the interface. The binding energies of the Yb 4d and O 1s spectra increased with increasing depth into the films. In the O 1s spectra, the organic bonds on the surface first decreased and then increased with increasing annealing temperature. Silicate formation at the interface was determined for the annealed samples. This affected the electrical performance of the capacitors. The calculated dielectric values range from 12.1 to 15.8. Interface level densities were found in the order of 10(12) cm(-2) and it did not exhibit frequency-dependent behavior. The calculated values for the effective charge densities varied between -24.19x10(11) - 7.03x10(11) cm(-2). It has been determined that mostly negative charges are trapped more for different capacitors. Finally, Fermi energy level, dopant concentration, diffusion potential and barrier heights were calculated.
Keywords: Rare-earth oxides; High-k dielectrics; EBPVD; Thin films; MOS Capacitor